Density regulation in Northeast Atlantic fish populations: Density dependence is stronger in recruitment than in somatic growth - Zimmermann, Fabian; Ricard, Daniel; Heino, Mikko (Journal of animal ecology, 2018)
Population regulation is a central concept in ecology, yet in many cases its presence and the underlying mechanisms are difficult to demonstrate. The current paradigm maintains that marine fish populations are predominantly regulated by density-dependent recruitment. While it is known that density-dependent somatic growth can be present too, its general importance remains unknown and most practical applications neglect it. This study aimed to close this gap by for the first time quantifying and comparing density dependence in growth and recruitment over a large set of fish populations. We fitted density-dependent models to time-series data on population size, recruitment and age-specific weight from commercially exploited fish populations in the Northeast Atlantic Ocean and the Baltic Sea. Data were standardized to enable a direct comparison within and among populations, and estimated parameters were used to quantify the impact of density regulation on population biomass. Statistically significant density dependence in recruitment was detected in a large proportion of populations (70%), whereas for density dependence in somatic growth the prevalence of density dependence depended heavily on the method (26% and 69%). Despite age-dependent variability, the density dependence in recruitment was consistently stronger among age groups and between alternative approaches that use weight-at-age or weight increments to assess growth. Estimates of density-dependent reduction in biomass underlined these results: 97% of populations with statistically significant parameters for growth and recruitment showed a larger impact of density-dependent recruitment on population biomass. The results reaffirm the importance of density-dependent recruitment in marine fishes, yet they also show that density dependence in somatic growth is not uncommon. Furthermore, the results are important from an applied perspective because density dependence in somatic growth affects productivity and catch composition, and therefore the benefits of maintaining fish populations at specific densities.
Keywords: Animals; populační dynamika; Population Density; zvířata; biomasa; hustota populace; Fishes; Atlantský oceán; ryby; Biomass; Population Dynamics; Atlantic Ocean